Pengaruh Future Time Perspective terhadap Career Maturity pada Mahasiswa Tingkat Akhir - Syifa Nur Zihan Zahra; Sartika, Dewi; Muhamad Arif Saefudin (Bandung Conference Series: Psychology Science, 2024)
Abstract. Final year students are at the transition stage where students are already required to be able to determine the type of work that suits their interests. On the other hand, the issue of career maturity is still a discussion at the level of students who should be more mature in determining their interests and goals for the future. future time perspective serves as a motivation for a person to engage in activities that can help achieve future results. A person who has a future perspective can see that they have a great opportunity in the future, besides that they will try harder to achieve their goals by improving and developing the skills they currently have. The purpose of this study is to examine how the influence of future time perspective variables on career maturity variables in final year students in Bandung. Type of causality research with a quantitative approach. The research subjects were 389 final year students aged between 18-25 years in Bandung. Hasna Putri's career maturity scale research measurement tool that refers to Super's theory and the FTP-I scale designed by Lang et al. (2002) which was later adapted by Medellu et al. (2020). The results of data analysis indicate that the FTP variable affects the career maturity variable by 43.2% and 56.8% is influenced by other variables. In addition, seen based on the results of the analysis using simple linear regression shows the positive direction of FTP on career maturity. The suggestion for this research is that students can participate in many activities, both on campus and outside, for example participating in internships, organizations, or hobbies that they like, in order to help students better understand their own interests and abilities. Abstrak. Mahasiswa tingkat akhir berada pada tahapan transition dimana mahasiswa sudah di tuntut untuk mampu menentukan jenis pekerjaan yang sesuai dengan minatnya. Disisi lain permasalahan mengenai career maturity masih menjadi pembahasan pada tingkat mahasiwa yang seharusnya sudah lebih matang menentukan minat dan tujuan untuk masa depannya. future time perspective berfungsi sebagai motivasi bagi seseorang untuk terlibat dalam kegiatan yang dapat membantu mencapai hasil di masa depan. Seseorang yang memiliki perspektif masa depan dapat melihat bahwa mereka memiliki kesempatan yang besar di masa depan, selain itu mereka akan berusaha lebih keras untuk mencapai tujuannya dengan meningkatkan dan mengembangkan keterampilan yang dimiliki saat ini. Tujuan dari penelitian ini yaitu ingin menguji bagaimana pengaruh variabel future time perspective terhadap variabel career maturity pada mahasiswa tingkat akhir di Bandung. Jenis penelitian kausalitas dengan pendekatan kuantitatif. Subjek penelitian sebanyak 389 mahasiswa tingkat akhir berusia antara 18-25 tahun di Bandung. Alat ukur penelitian skala career maturity Hasna Putri yang mengacu pada teori Super dan skala FTP-I yang dirancang oleh Lang et al. (2002) yang kemudian diadaptasi Medellu et al. (2020). Hasil analisis data mengindikasikan bahwa variabel FTP berpengaruh pada variabel career maturity sebesar 43.2% dan 56.8% dipengaruhi oleh variabel lainnya. Selain itu, dilihat berdasarkan hasil analisis menggunakan regresi linier sederhana menunjukan arah positive FTP terhadap career maturity. Saran untuk penelitian ini agar mahasiwa dapat mengikuti banyak kegiatan, baik di kampus maupun di luar, contohnya mengikuti magang, organisasi, atau hobi yang disukai, agar dapat membantu mahasiswa lebih memahami minat dan kemampuannya sendiri.